A three-year prospective cohort study evaluating implant stability utilising the Osstell® and Periotest™ devices - Reynolds, Ian; Winning, Lewis; Polyzois, Ioannis (Frontiers in Dental Medicine, 2023)
Objectives To investigate implant stability measurements from two different devices and at three different time points in order to determine their level of correlation. To also evaluate the influence of a range of clinical characteristics on the values produced by the devices at these three time points. Materials & Methods Measurements were recorded at implant placement (T1), implant exposure (T2) and at 3 years from implant placement (T3). A range of clinical data was collected including patient demographics and site characteristics. Stability measurements and clinical characteristics were recorded for 29 patients and 68 dental implants at T1, subsequent stability measurements were recorded for 67 implants at T2 and 58 implants at T3. Correlation testing between the Osstell® and Periotest™ devices was carried out utilising Spearman's rank correlation for each time point. Analysis of the difference between clinical factors and stability measurements was compared using Kruskal-Wallis test for each variable and time point. Results A single dental implant failed shortly after second stage surgery for an overall survival rate of 98% during the study timeline. The median ISQ value was 73.25 (IQR 67–75) at T1 and 74 (IQR 70.5–77) at T3. The median Periotest value was −4 (IQR −6, −2) at T1 and −6 (IQR −7, −5) at T3. The range of ISQ values observed was 50 (39–89) ISQ at T1 and decreased to 21 (61–82) ISQ at T3. The Periotest values ranged from 37 (29 to −8) at T1 and decreased to 6 (−2 to −8) at T3. A weak to moderate correlation was observed between mean ISQ and Periotest values across time points T1, T2 and T3, (r = −0.26, p = 0.05), (r = −0.35, p < 0.01) and (r = −0.28, p = 0.04) respectively. Conclusions Based on the results of this study there was a weak to moderate level of correlation between values recorded between the two measurement devices at implant placement, implant exposure and three years following placement. For both the Osstell® and Periotest™ a narrowing of the range of stability values was observed from T1 to T3. In general, Periotest™ seemed to be more sensitive in highlighting differences in measurements affected by local conditions.